Phase I randomized study of KHK4083, an anti‐OX40 monoclonal antibody, in patients with mild to moderate plaque psoriasis. (14th June 2017) - Papp, K.A.; Gooderham, M.J.; Girard, G.; Raman, M.; Strout, V.
Abstract: Background: OX40 (CD134) is expressed in lesional but not healthy skin of patients with psoriasis. KHK4083 is a fully human monoclonal antibody against OX40. Objective: The primary aim of this first‐in‐human phase 1 study was to determine the safety and tolerability of ascending single doses of KHK4083 in patients with mild to moderate plaque psoriasis. Secondary aims were to determine the pharmacokinetics and immunogenicity of KHK4083, and an exploratory objective was to assess clinical activity. Methods: In phase 1a, single doses of KHK4083 0.003 and 0.001 mg/kg IV were administered open label in two cohorts (each n = 6). Phase 1b had a multicentre, randomized, double‐blind, placebo‐controlled, ascending single‐dose design in seven cohorts. Randomization was performed 3 : 1 to KHK4083 ( n = 6) or placebo ( n = 2) within each cohort. Ascending doses of KHK4083 were 0.03, 0.1, 0.3, 1.0, 3.0 and 10 mg/kg IV, and 1.0 mg/kg SC. Results: There were no severe or serious adverse events (AEs), or discontinuations because of AEs. The most frequent treatment‐related AEs in the 55 patients who received KHK4083 were mild or moderate chills (9.1%), and infusion/injection site reactions (7.3%). No clinically meaningful or dose‐related changes from baseline in laboratory values, vital signs, ECG recordings or physical examinations were observed. Some KHK4083 recipients (10/54) developed anti‐KHK4083 antibodies following treatment. Mean elimination half‐life ( t 1/2 ) increased with dose, maximum serum concentration increased in a dose‐proportional manner, and area under the serum concentration–time curve increased in a more than dose‐proportional manner with increasing IV dose. Absolute bioavailability following SC administration was 73%. There was some indication of improvement in Psoriasis Area Severity Index (PASI) and sPGA scores at the highest IV doses (1.0 and 10 mg/kg) and the SC dose (1.0 mg/kg). The largest PASI 50 response and improvement in sPGA score ≥2 occurred with KHK4083 1.0 mg/kg SC. Conclusion: KHK4083 administration as a single dose up to 10 mg/kg IV or 1.0 mg/kg SC was generally safe and well tolerated in patients with mild to moderate plaque psoriasis with no dose‐limiting AEs.